Perindopril effects on circadian heart rate variability in patients with coronary heart disease and stable angina - N. A. Shardanov; E. K. Arsagova; L. M. Batyrbekova; M. Kh. Kurdanova; Kh. A. Kurdanov (Кардиоваскулярная терапия и профилактика)
Aim. To study the effects of ACE inhibitor perindopril on circadian dynamic of heart rate variability (HRV) in patients with coronary heart disease (CHD) and stable effort angina. Material and methods. The study included 68 patients with stable effort angina, without myocardial infarction in anamnesis, as well as 30 controls. Circadian HRV was assessed by Holter monitoring method, during isosorbide dinitrate and aspirin therapy, and 31 days after adding perindopril (4-8 mg/d). Results. At baseline, temporal and spectral HRV parameters were decreased in CHD patients with stable angina, improving during perindopril therapy (4-8 mg/d). Positive dynamics was maximal for parasympathetic activity markers. Perindopril therapy also reduced ventricular extrasystole number in CHD patients. Conclusion. Perindopril (4-8 mg/d) improved circadian BP dynamics in CHD patients with stable effort angina, especially in individuals with advanced functional classes. Perindopril also demonstrated antiarrhythmic effect.